PHYSICAL TRAINING TO PREVENT SPORTS INJURIES IN ATHLETES - Zhou,Guohai (2022)
ABSTRACT Introduction: The purpose of physical training for athletes is to maintain and improve athletes’ coordination, reaction ability, spatial orientation, anti-load ability, endurance, and other abilities. But the problem of injury in sports must be solved. Objective: To investigate the causes of athletes’ injuries during physical training and proposes solutions for them. Methods: A questionnaire was applied to athletes to learn about their injuries in recent sports and their methods to avoid injuries. Results: Insufficient warm-up is the most common cause of injury. Other causes include site factors, fatigue, and excessive load. Sports injuries are the most common in extracurricular activities, while injuries are the least in sports training. The season in which the most damage occurs is winter, followed by autumn, and while spring shows the least injuries. Conclusion: The cause of sports injuries in physical training is related to insufficient warm-up activities. Physical training instructors should continuously improve their teaching level and provide athletes with the correct knowledge and skills to prevent sports injuries and protect themselves. As a result, the probability of sports injuries can be reduced as much as possible. Level of evidence II; Therapeutic studies - investigation of treatment results.